A Comparative Analysis of Surgical Outcomes in Free Flap Reconstruction for Head and Neck Cancer - Fazal Wahid, Vijay Kumar Khatri, Muhammad Irfan Khan, Aziz Ullah Khan, Jamshed Khan, Muhammad Moiz Ullah Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Free flap reconstruction has become a cornerstone in the surgical management of headand neck cancer, particularly for patients requiring resection of significant soft tissue or bone. The outcomes of free flap procedures can vary based on multiple factors, including patient